Sikap Sosial Keagamaan Siswa dalam Bingkai Moderasi Beragama - Firdaus, Indra Cahya; Muflikhah, Umi (Balai Penelitian dan Pengembangan Agama Semarang, 2025)
The government’s efforts to promote religious moderation as a core societal value have been consistently pursued in recent years. However, the landscape of religious freedom in Indonesia continues to face significant challenges, with intolerance still surfacing in various forms. According to the Setara Institute’s 2024 report, there were 217 documented incidents in 2023 related to violations of freedom of religion and belief, totaling 329 individual acts. This study aims to explore the characteristics of socio-religious attitudes among students of public senior high school (SMAN) and students of state Islamic senior high school (MAN). The primary objective of this study is to examine the patterns of socio-religious attitudes among students attending both general and Islamic public senior secondary schools. Employing a quantitative research approach, the study seeks to obtain precise and representative measurements that closely reflect social realities. Statistical analysis is used to assess and compare students’ socio-religious attitudes across two distinct school types: public senior high schools (SMAN) and public Islamic senior high schools (MAN) in Jakarta. The normality test results revealed that the data did not conform to a normal distribution. Consequently, the analysis was performed using the Mann-Whitney non-parametric test. The outcome indicated a significance level of 0.625, surpassing the conventional alpha threshold of 0.05. This finding suggests the absence of a statistically meaningful difference in socio-religious attitudes between students attending public senior high schools (SMAN) and those enrolled in public Islamic senior high schools (MAN). The results imply that students generally demonstrate a constructive and inclusive orientation towards matters related to religious belief, the institutionalization of religious law, and tolerance.